Evaluation in discussion sessions of conference presentations: theoretical foundations for a multimodal analysis - Querol-Julián, Mercedes; Fortanet-Gómez, Inmaculada (Kalbotyra, 2016)
Discussions sessions have not received much attention within the genre of conference presentations. In this paper, we present the theoretical framework that underlies the approach followed to analyse the multimodal expression of evaluation. Then, an example of the application of the study has been considered necessary to understand it. Corpus linguistics provided the indications to collect the corpus, annotate it and find the appropriate software to digitalise the relevant information for the study. Secondly, genre studies and conversational analysis gave the clues to establish a structure in the linguistic expressions found in the discussion sessions of paper presentations. Thirdly, systemic functional linguistics and pragmatics provided the basis for an evaluative scheme that could be applied to the academic discourse of the corpus, considering its multimodal nature. Fourthly, the tools to observe the non-verbal communication associated with evaluative language were found in multimodal discourse analysis studies. All together, the application of these variables led to an original study of discussion sessions, which deployed interesting results.